The association of child maltreatment and systemic inflammation in adulthood: A systematic review - Kerr, Daniel M. (PLoS One, 2021)
INTRODUCTION: Child maltreatment (CM) is associated with mental and physical health disorders in adulthood. Some studies have identified elevated markers of systemic inflammation in adult survivors of CM, and inflammation may mediate the association between CM and later health problems. However, there are methodological inconsistencies in studies of the association between CM and systemic inflammation and findings are conflicting. We performed a systematic review to examine the association of CM with systemic inflammation in adults. METHODS: A pre-registered systematic review was performed following PRISMA guidelines. Medline, Embase, Scopus and PsychInfo were searched for studies of the association of CM with blood markers of inflammation in adults. Quality was assessed using the Crowe Critical Appraisal Tool. We had intended to perform a meta-analysis, but this was not possible due to variation in study design and reporting. RESULTS: Forty-four articles met criteria for inclusion in the review. The most widely reported biomarkers were C-Reactive Protein (CRP) (n = 27), interleukin-6 (IL-6) (n = 24) and Tumour Necrosis Factor-alpha (TNF-a) (n = 17). Three studies were prospective (all relating to CRP) and the remainder were retrospective. 86% of studies were based in high income countries. In the prospective studies, CM was associated with elevated CRP in adulthood. Results of retrospective studies were conflicting. Methodological issues relating to the construct of CM, methods of analysis, and accounting for confounding or mediating variables (particularly Body Mass Index) may contribute to the uncertainty in the field. CONCLUSIONS: There is some robust evidence from prospective studies that CM is associated with elevated CRP in adulthood. We have identified significant methodological inconsistencies in the literature and have proposed measures that future researchers could employ to improve consistency across studies. Further prospective, longitudinal, research using robust and comparable measures of CM with careful consideration of confounding and mediating variables is required to bring clarity to this field.